(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
The article emphasizes that today social danger of this crime in the form of organized crime and corruption is further increased by the fact that it becomes extremely dangerous, the state becomes dangerous by the fact that it causes the consequences of the crisis of society also cause the characteristics of risk